MXene-coated high-entropy composite cathode material and preparation method thereof, and lithium battery

CN121394352BActive Publication Date: 2026-10-30TIANFU JIANGXI LAB
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511534596.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-24
Publication Date
2026-10-30
Estimated Expiration
2045-10-24

AI Technical Summary

Technical Problem

[0006]为了解决富锂锰基正极材料现有体相掺杂和表面包覆技术中表面氧释放高、正极材料与包覆层易发生剥离以及容量保持率低、循环性能差的问题,本发明提供一种MXene包覆高熵复合正极材料,其包括高熵层状结构材料和MXene梯度包覆层,所述MXene梯度包覆层依次通过化学键合和物理吸附以梯度包覆于所述高熵层状结构材料之外;其中,所述高熵层状结构材料中包括富锂锰基前驱体与高熵掺杂金属盐,所述高熵掺杂金属盐中的金属包括Cu、Fe、Mo、Ag、Au、Al、Mg、Nb、Hf、Ta、Cr、Ge中的至少五种,且所述高熵层状结构材料由多孔状的高熵金属盐复合前驱体粉末经烧结形成;所述MXene梯度包覆层的材质包括Ti3C2Tx、V2CTx、V2NTx、Mo2CTx、Ti4N3Tx、Nb4C3Tx中的一种或多种的组合;其中,所述MXene梯度包覆层依次通过化学键合和物理吸附以梯度包覆于所述高熵层状结构材料之外,具体为:将所述具有层状结构的高熵材料与所述MXene分散液按第一质量比1:(18-22)在50℃-60℃下搅拌混合5-6 h,随后离心分离,真空干燥形成化学键合MXene包覆层得到MXene初级包覆高熵材料;将MXene初级包覆高熵材料与所述MXene分散液按第二质量比1:(0.1-0.3)混合,室温超声处理,再经过冷冻干燥完成物理吸附形成所述MXene梯度包覆层,得到MXene包覆高熵体材料

Benefits of technology

1.本发明所提供的一种MXene包覆高熵复合正极材料,包括高熵层状结构材料和MXene梯度包覆层。通过高熵层状结构材料设计与MXene梯度包覆层的协同策略,显著提升了富锂锰基正极材料的结构稳定性与电化学性能。通过高熵体相设计与多元素协同掺杂,有效解决了富锂锰基正极材料在循环过程中因阳离子混排和相变导致的结构崩塌问题,优化晶格稳定性,减少不可逆相变,从而显著延长材料的循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121394352B_ABST
    Figure CN121394352B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of battery, and particularly relates to a MXene-coated high-entropy composite cathode material, a preparation method thereof and a lithium battery. The present application provides a MXene-coated high-entropy composite cathode material, which comprises a high-entropy layered structure material and a MXene gradient coating layer. The MXene-coated high-entropy composite cathode material has good thermal stability, good conductivity and high capacity retention rate. The present application provides a preparation method of the MXene-coated high-entropy composite cathode material. The method significantly improves the structural stability and electrochemical performance of the MXene-coated high-entropy composite cathode material through the synergistic strategy of the high-entropy layered structure material design and the MXene gradient coating layer. The MXene-coated high-entropy composite cathode material provided by the present application and the MXene-coated high-entropy composite cathode material prepared by the preparation method of the MXene-coated high-entropy composite cathode material provided by the present application are applied to the lithium battery, and the lithium battery has stable performance and good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to an MXene-coated high-entropy composite cathode material, its preparation method, and a lithium battery. Background Technology

[0002] Lithium-rich manganese-based cathode materials are considered a core candidate for next-generation high-energy-density batteries due to their ultra-high specific capacity (>300 mAh / g). However, their commercialization faces the following key bottlenecks: 1. Structural degradation: During cycling, the layered structure undergoes an irreversible transformation to the spinel / rock salt phase, resulting in voltage decay (>0.5 V / 100 cycles) and capacity loss.

[0003] 2. Oxygen release risk: Under high voltage (>4.5 V), lattice oxygen escapes (O2evolution), triggering electrolyte oxidation and thermal runaway (TGA-DSC test shows that the oxygen release initiation temperature is <250℃).

[0004] 3. Kinetic hysteresis: Low electronic conductivity (<10) ﹣5 S / cm) and lithium-ion diffusion coefficient (<10) ﹣14 The rate performance is poor (2C capacity retention <50%) due to the speed of cm² / s.

[0005] To address these challenges, existing technologies mainly focus on two strategies: bulk doping and surface coating, but significant drawbacks remain: Bulk doping technology: through Al 3+ / Mg 2+ Co-doping stabilizes the layered structure of lithium-rich manganese-based cathode materials, reducing voltage decay to 0.3 V after 100 cycles. However, this method has limited effectiveness; excessive doping leads to a significant capacity decrease and cannot suppress surface oxygen release (TOF-SIMS testing shows that the surface oxygen loss rate of the doped material is still >15%). Metal oxide coating: Atomic layer deposition (ALD) was used to coat the surface of lithium-rich manganese particles with a 2-5 nm Al₂O₃ layer, increasing the electrolyte decomposition initiation voltage from 4.3 V to 4.5 V. The drawback of this method is the insulating coating layer (Al₂O₃ conductivity <10). ﹣ 10 The S / cm ratio leads to a surge in interface resistance (EIS shows an increase in Rct >200%), resulting in deteriorated rate performance (4C capacity retention <40%). Furthermore, the weak interfacial bonding between the coating layer and the cathode particles causes peeling during cycling due to volume changes (SEM shows coating coverage <50% after 100 cycles). Carbon-based material coating: A 10nm thick carbon nanotube layer was coated onto the surface of a lithium-rich manganese-based cathode material using a ball milling method, increasing the electronic conductivity to 10. ﹣2S / cm. However, carbon materials undergo a reduction reaction with the cathode surface under high voltage, accelerating the formation of oxygen vacancies. The carbon layer and the oxide cathode are mainly physically bonded, and the interface is easily delaminated during high-temperature cycling (>60℃). Summary of the Invention

[0006] To address the problems of high surface oxygen release, easy delamination between the cathode material and the coating layer, low capacity retention, and poor cycle performance in existing bulk doping and surface coating technologies for lithium-rich manganese-based cathode materials, this invention provides an MXene-coated high-entropy composite cathode material, comprising a high-entropy layered structure material and an MXene gradient coating layer. The MXene gradient coating layer is sequentially coated on the high-entropy layered structure material through chemical bonding and physical adsorption. The high-entropy layered structure material comprises a lithium-rich manganese-based precursor and a high-entropy doped metal salt. The high-entropy doped metal salt contains at least five metals selected from Cu, Fe, Mo, Ag, Au, Al, Mg, Nb, Hf, Ta, Cr, and Ge. The high-entropy layered structure material is formed by sintering porous high-entropy metal salt composite precursor powder. The MXene gradient coating layer is made of Ti3C2T. x V2CT x V2NT x Mo2CT x Ti4N3T x Nb4C3T x One or more combinations thereof; wherein the MXene gradient coating layer is sequentially coated on the high-entropy layered structure material by chemical bonding and physical adsorption, specifically: the high-entropy material with the layered structure is mixed with the MXene dispersion at a first mass ratio of 1:(18-22) at 50℃-60℃ for 5-6 h, then centrifuged and vacuum dried to form a chemically bonded MXene coating layer to obtain the MXene primary coated high-entropy material; the MXene primary coated high-entropy material is mixed with the MXene dispersion at a second mass ratio of 1:(0.1-0.3), ultrasonically treated at room temperature, and then freeze-dried to complete the physical adsorption to form the MXene gradient coating layer to obtain the MXene coated high-entropy bulk material.

[0007] Furthermore, the thickness of the MXene gradient coating layer is 2-20 nm.

[0008] To address the aforementioned technical problems, this invention also provides a method for preparing MXene-coated high-entropy composite cathode materials, specifically comprising the following steps: mixing a lithium-rich manganese-based precursor with a high-entropy doped metal salt, adding a complexing agent and stirring to form a sol, and spray-drying to obtain a porous high-entropy metal salt composite precursor powder; subjecting the porous high-entropy metal salt composite precursor powder to primary sintering, followed by secondary sintering, and then cooling and ball milling to obtain a high-entropy layered structure material; providing a MAX phase material and an etching solution, etching the MAX phase material with the etching solution, and obtaining an MXene dispersion containing single-layer or few-layer MXene nanosheets through intercalation and ultrasonic exfoliation; mixing the high-entropy material with the layered structure and the MXene dispersion at a first mass ratio of 1:(18-22) at 50℃-60℃ for 5-6 minutes. h, then centrifuged and vacuum dried to form a chemically bonded MXene coating layer to obtain a primary MXene-coated high-entropy material; the primary MXene-coated high-entropy material and the MXene dispersion were mixed at a second mass ratio of 1:(0.1-0.3), ultrasonicated at room temperature, and then freeze-dried to complete physical adsorption to form the MXene gradient coating layer, to obtain an MXene-coated high-entropy bulk material; and the MXene-coated high-entropy bulk material was heated to a first temperature under a protective atmosphere and maintained for a preset time, then heated to a second temperature under a reducing atmosphere for reduction treatment and then cooled to room temperature to obtain an MXene-coated high-entropy composite cathode material; the MXene-coated high-entropy composite cathode material as described above was prepared.

[0009] Furthermore, in the step of mixing a lithium-rich manganese-based precursor with a high-entropy doped metal salt, adding a complexing agent and stirring to form a sol, and then spray drying to obtain a high-entropy metal salt composite precursor powder: the molar ratio of the lithium-rich manganese-based precursor to the high-entropy doped metal salt is 1:(0.8-1.2), the molar ratio of the complexing agent to the metal in the high-entropy doped metal salt is (1.4-1.6):1; and / or, the inlet air temperature of the spray drying process is 200℃-300℃, and the outlet air temperature is 100℃-200℃.

[0010] Furthermore, in the step of primary sintering of the high-entropy metal salt composite precursor powder followed by secondary sintering, the primary sintering conditions are as follows: heating to 400℃-700℃ at a heating rate of 4-6℃ / min and holding for 1-3 hours; the secondary sintering conditions are as follows: heating to 800℃-1000℃ at a heating rate of 2-4℃ / min under oxygen-permeable conditions and calcining for 11-13 hours.

[0011] Furthermore, in the steps of providing MAX phase material and etching solution, etching the MAX phase material with the etching solution, and obtaining an MXene dispersion containing monolayer or few-layer MXene nanosheet material through intercalation and ultrasonic exfoliation, the etching conditions are as follows: adding the MAX phase material to an etching solution with a concentration of 30%-40% and stirring at 30℃-40℃ for 40-48 h; the etching solution is hydrofluoric acid or an acid solution containing fluorine salts; and / or, the ultrasonic exfoliation conditions are exfoliation at a power of 300-400W for 2-3 h.

[0012] Further, in the step of heating the MXene-coated high-entropy bulk material to a first temperature and maintaining it for a preset time under a protective atmosphere, then heating it to a second temperature under a reducing atmosphere for reduction treatment, and finally cooling it to room temperature to obtain the MXene-coated high-entropy composite cathode material: the first temperature is 300-500℃, the second temperature is 600-700℃; and / or, the preset time is 2-3 h, and the reduction treatment time is 1-2 h.

[0013] Furthermore, the centrifugation conditions are 5000-6000 rpm for 5-6 min, the vacuum drying conditions are 80℃-90℃ for 10-12 h, and the freeze-drying conditions are -50℃ to -60℃ for 20-24 h.

[0014] To solve the above-mentioned technical problems, the present invention also provides a lithium battery, the lithium battery comprising the MXene-coated high-entropy composite cathode material as described above or the MXene-coated high-entropy composite cathode material prepared by the preparation method of the MXene-coated high-entropy composite cathode material as described above.

[0015] Compared with the prior art, the MXene-coated high-entropy composite cathode material and its preparation method, as well as the lithium battery provided by the present invention, have the following beneficial effects: 1. This invention provides an MXene-coated high-entropy composite cathode material, comprising a high-entropy layered structure material and an MXene gradient coating layer. Through a synergistic strategy of high-entropy layered structure material design and MXene gradient coating layer, the structural stability and electrochemical performance of lithium-rich manganese-based cathode materials are significantly improved. By employing high-entropy bulk phase design and multi-element synergistic doping, the structural collapse problem caused by cation mixing and phase transitions during cycling of lithium-rich manganese-based cathode materials is effectively solved, optimizing lattice stability, reducing irreversible phase transitions, and thus significantly extending the cycle life of the material.

[0016] 2. The present invention provides an MXene-coated high-entropy composite cathode material, wherein the thickness of the MXene gradient coating layer is 2-20 nm. At this thickness, MXene nanosheets are more likely to form a uniform thin layer. A suitable thin layer can provide a fast conduction path for electrons without hindering ions, improve conductivity and electrode-electrolyte interface stability, effectively construct a stable surface layer, block oxygen diffusion paths and reduce surface oxygen activity, and effectively inhibit oxygen release.

[0017] 3. The present invention provides a method for preparing an MXene-coated high-entropy composite cathode material. A high-entropy layered structure material is prepared through a high-temperature solid-state reaction. An MXene gradient coating layer is then constructed on the high-entropy layered structure material using an MXene dispersion, which enhances its mechanical and chemical stability. The high mechanical strength of the high-entropy layered structure material combined with the flexible buffering effect of the MXene gradient coating layer improves the material's structural integrity and electrolyte compatibility, reduces crack formation and interfacial decomposition, and minimizes particle pulverization and interfacial side reactions caused by volume changes during charging and discharging. Simultaneously, it enhances the material's thermal stability and high-temperature safety.

[0018] 4. The present invention provides a method for preparing MXene-coated high-entropy composite cathode material by mixing lithium-rich manganese-based precursor with high-entropy doped metal salt in a molar ratio, adding a complexing agent and stirring to form a sol, and then spray drying to obtain high-entropy metal salt composite precursor powder. This method can achieve atomic-level uniform dispersion of multiple metal elements, providing a precursor basis for the subsequent formation of high-entropy layered structures.

[0019] 5. The present invention provides a method for preparing MXene-coated high-entropy composite cathode material, which involves primary sintering of high-entropy metal salt composite precursor powder, followed by secondary sintering, and forming a high-crystallinity high-entropy layered structure material through high-temperature solid-state reaction, thereby ensuring the structural stability and phase uniformity of the material.

[0020] 6. The present invention provides a method for preparing MXene-coated high-entropy composite cathode materials, which, through the synergistic treatment of intercalation and ultrasonic exfoliation, yields an MXene dispersion containing monolayer or few-layer MXene nanosheets. Successful intercalation of the intercalating agent mechanically increases the interlayer spacing of the MXene material and significantly weakens the van der Waals forces between layers, making the sheets easier to separate. After the intercalating agent expands the interlayer structure, ultrasonic treatment provides energy for the final separation of the sheets. The synergistic treatment of intercalation and ultrasonic exfoliation effectively exfoliates MXene sheets, yielding monolayer or few-layer MXene nanosheet materials.

[0021] 7. The present invention provides a method for preparing an MXene-coated high-entropy composite cathode material. An MXene gradient coating layer is constructed on the surface of a high-entropy layered material using an MXene dispersion. Through the dual effects of chemical bonding and physical adsorption, the MXene coating layer further fills micropores and defects on the material surface, forming a continuous and dense protective layer, reducing the density of side reaction active sites, and improving interfacial stability. The synergistic effect of low specific surface area and a dense surface layer reduces the occurrence of irreversible side reactions, contributing to improved coulombic efficiency and capacity retention of the battery.

[0022] 8. The present invention provides a method for preparing an MXene-coated high-entropy composite cathode material. This method utilizes an MXene dispersion containing monolayer or few-layer MXene nanosheets to construct an MXene gradient coating layer. Since the MXene is in a monolayer or few-layer state, it possesses a large specific surface area, providing more contact sites for charge carriers such as lithium ions, significantly improving capacitance and energy storage capacity. The high conductivity of monolayer or few-layer MXene nanosheets is used to construct a surface conductive network, effectively solving the problems of low electronic conductivity and high interfacial charge transport resistance in traditional lithium-rich manganese-based cathode materials, and significantly improving the material's cycle performance.

[0023] 9. The present invention provides a method for preparing an MXene-coated high-entropy composite cathode material. After constructing the MXene gradient coating layer, the material is heated to a first temperature under a protective atmosphere and maintained for a preset time. Then, it is heated to a second temperature under a reducing atmosphere for reduction treatment and cooled to room temperature to obtain the desired MXene-coated high-entropy composite cathode material. High-temperature annealing optimization of the MXene-coated high-entropy composite cathode material through the above process can effectively eliminate surface defects in the MXene gradient coating layer and improve the conductivity and interfacial bonding stability of the coating layer.

[0024] 10. The present invention also provides a lithium battery comprising the above-described MXene-coated high-entropy composite cathode material or an MXene-coated high-entropy composite cathode material prepared by the above-described method for preparing the MXene-coated high-entropy composite cathode material. The lithium battery exhibits good coulombic efficiency and capacity retention, and good cycle performance. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1This is a schematic diagram of an MXene-coated high-entropy composite cathode material provided in the first embodiment of the present invention.

[0027] Figure 2 This is a schematic diagram of the structure of an MXene-coated high-entropy composite cathode material provided in the first embodiment of the present invention.

[0028] Figure 3 The flowchart illustrates the specific steps of a method for preparing an MXene-coated high-entropy composite cathode material according to the second embodiment of the present invention.

[0029] Figure 4 This is a schematic diagram illustrating the formation process of the high-entropy layered structure material and the MXene gradient coating layer in a method for preparing an MXene-coated high-entropy composite cathode material according to the second embodiment of the present invention.

[0030] Figure 5 The XRD pattern is for Experimental Example 1 provided by the present invention.

[0031] Explanation of reference numerals in the attached diagram: 1. High-entropy layered structure material; 2. MXene gradient coating layer; 11. Lithium-rich manganese-based precursor. Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0033] In the embodiments provided by this invention, it should be understood that "B corresponding to A" means that B is associated with A, and B can be determined based on A. However, it should also be understood that determining B based on A does not mean determining B solely based on A; B can also be determined based on A and / or other information.

[0034] It should be understood that the phrase "one embodiment" or "an embodiment" throughout the specification means that a specific feature, structure, or characteristic related to the embodiment is included in at least one embodiment of the invention. Therefore, "in one embodiment" or "in an embodiment" appearing throughout the specification does not necessarily refer to the same embodiment. Furthermore, these specific features, structures, or characteristics can be combined in any suitable manner in one or more embodiments. Those skilled in the art should also recognize that the embodiments described in the specification are optional embodiments, and the actions and modules involved are not necessarily essential to the invention.

[0035] In various embodiments of the present invention, it should be understood that the sequence number of each process does not necessarily imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process defined by the present invention.

[0036] The flowcharts and block diagrams in the accompanying drawings illustrate methods and possible architectures, functions, and operations according to various embodiments of this application. In this regard, each block in the flowchart or block diagram may represent part of a step. It should also be noted that in some alternative implementations, the functions indicated in the blocks may occur in a different order than those indicated in the drawings. For example, two consecutively indicated blocks may actually be executed substantially in parallel, or they may sometimes be executed in reverse order, depending on the functions involved.

[0037] Please see Figure 1 The first embodiment of the present invention provides an MXene-coated high-entropy composite cathode material, comprising a high-entropy layered structure material 1 and an MXene gradient coating layer 2. The MXene gradient coating layer 2 is coated on the high-entropy layered structure material 1 by chemical bonding and physical adsorption gradient. The high-entropy layered structure material 1 comprises a lithium-rich manganese-based precursor and a high-entropy doped metal salt. The metal in the high-entropy doped metal salt includes at least five of the following: Cu, Fe, Mo, Ag, Au, Al, Mg, Nb, Hf, Ta, Cr, and Ge. The material of the MXene gradient coating layer 2 includes Ti3C2T. x V2CT x V2NT x Mo2CT x Ti4N3T x Nb4C3T x One or more combinations thereof.

[0038] Please see Figure 2 This is a schematic diagram of the structure of an MXene-coated high-entropy composite cathode material according to the first embodiment of the present invention, which includes a high-entropy layered structure material 1 and an MXene gradient coating layer 2.

[0039] In some embodiments of the present invention, the thickness of the MXene gradient coating layer 2 is 2-20nm, and may be 2-5nm, 5-10nm, 12-18nm, or 15-20nm, specifically 2nm, 5nm, 10nm, 15nm, or 20nm.

[0040] Please see Figure 3 The second embodiment of the present invention provides a method for preparing MXene-coated high-entropy composite cathode material, which specifically includes the following steps: Step S1: The lithium-rich manganese-based precursor is mixed with a high-entropy doped metal salt in a molar ratio, a complexing agent is added and stirred to form a sol, and the high-entropy metal salt composite precursor powder is obtained by spray drying. Step S2: The high-entropy metal salt composite precursor powder is subjected to primary sintering, followed by secondary sintering, cooling, and ball milling to obtain a high-entropy layered structure material. Step S3: Provide MAX phase material and etching solution, etch the MAX phase material with etching solution, and obtain MXene dispersion containing monolayer or few-layer MXene nanosheet material through intercalation and ultrasonic exfoliation; Step S4: Construct an MXene gradient coating layer on the surface of the high-entropy layered structure material using an MXene dispersion to obtain an MXene-coated high-entropy bulk material; and Step S5: The MXene-coated high-entropy bulk material is heated to a first temperature under an inert atmosphere and maintained for a preset time. Then, it is heated to a second temperature under a reducing atmosphere for reduction treatment and then cooled to room temperature to obtain the desired MXene-coated high-entropy composite cathode material.

[0041] Please see Figure 4 In the preparation method of MXene-coated high-entropy composite cathode material provided in the second embodiment of the present invention, a high-entropy layered structure material 1 is formed through steps S1 and S2, and then an MXene gradient coating layer 2 is formed through steps S3-S5. The high-entropy layered structure material 1 is prepared by mixing a lithium-rich manganese-based precursor 11 with a high-entropy doped metal salt and then performing a high-temperature solid-state reaction. The MXene gradient coating layer 2 is then constructed on the high-entropy layered structure material using an MXene dispersion. Through the synergistic strategy of forming the high-entropy layered structure material 1 and the MXene gradient coating layer 2, the structural stability and electrochemical performance of the lithium-rich manganese-based cathode material can be significantly improved.

[0042] It can be understood that the aforementioned lithium-rich manganese-based precursor is xLi₂MnO₃·(1-x)LiMO₂. In this context, M in the LiMO₂ component represents one or more transition metals, typically Ni, Co, Mn, etc., such as LiNi. 0.5 Mn 0.5 O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2, etc., and LiMO2 components are typical cathode materials with a layered structure, providing reversible lithium-ion insertion / extraction capacity. Li2MnO3 components are initially electrochemically inert, possessing a layered structure similar to LiMO2, where manganese ions occupy 2 / 3 of the positions in the transition metal layer, and lithium ions occupy the remaining 1 / 3. This ordered arrangement makes it stable at low voltages. When charged above 4.5 V, Li2MnO3 components are activated, at which point lithium and oxygen precipitate from the lattice to form Li2O, while the valence state of manganese changes, leaving vacancies in the material, thus providing additional ultra-high capacity in subsequent cycles. "x" represents the molar ratio of the two components, typically between 0.1 and 0.5, and this ratio determines the material's capacity, voltage, and stability.

[0043] It is understood that in step S1 above, the metal in the high-entropy doped metal salt includes at least five of the following: Cu, Fe, Mo, Ag, Au, Al, Mg, Nb, Hf, Ta, Cr, and Ge. The high-entropy doped metal salt can be a nitrate metal salt, such as ferric nitrate (Fe(NO3)3), aluminum nitrate (Al(NO3)3), calcium nitrate (Ca(NO3)2), strontium nitrate (Sr(NO3)2), barium nitrate (Ba(NO3)2), zinc nitrate (Zn(NO3)2), nickel nitrate (Ni(NO3)2), cobalt nitrate (Co(NO3)2), etc.; the high-entropy doped metal salt can be a sulfate metal salt, such as ferric sulfate (Fe2(SO4)3), aluminum sulfate (Al2(SO4)3), titanium sulfate (Ti(SO4)2), etc.; furthermore, the high-entropy doped metal salt can also be a chloride (such as NiCl2, CrCl3), an acetate (such as Mg(CH3COO)2), etc. In this invention, metal nitrate salts are used as an example because nitrate ions are easily decomposed and do not easily remain during calcination, resulting in high-entropy layered structure materials with better performance. In this invention, by uniformly dispersing multiple metal elements, atomic-level mixing of high-entropy doping is ensured, providing a precursor basis for the subsequent formation of high-entropy layered structures.

[0044] In step S1 above, the molar ratio of the lithium-rich manganese-based precursor to the high-entropy doped metal salt is 1:(0.8-1.2). The molar ratio can be 1:(0.8-0.9), 1:(0.9-1), 1:(1-1.1), or 1:(1.1-1.2), etc. Specifically, it can be 1:0.8, 1:0.9, 1:1, 1:1.1, or 1:1.2.

[0045] In step S1 above, specifically, in the step of adding a complexing agent and stirring to form a sol, citric acid (C8H8O7) can be added as a complexing agent, deionized water as a solvent, and nitrate metal salt as the high-entropy doped metal salt, as nitrate metal salt has a better complexing effect with citric acid. The molar ratio of the complexing agent to the metal in the high-entropy doped metal salt is (1.4-1.6):1, and can further be (1.4-1.5):1, (1.45-1.5):1, (1.5-1.6):1, etc., specifically 1.4:1, 1.45:1, 1.5:1, or 1.6:1. During stirring, citric acid partially ionizes, which can effectively complex metal ions and avoid precipitation. During stirring, the water in the mixed sol continuously evaporates, the sol gradually concentrates, and the viscosity increases significantly.

[0046] In step S1 above, the spray drying process specifically includes using an airflow spray dryer. This airflow spray dryer has an atomizing device, which employs a dual-flow nozzle. The airflow spray dryer uses a parallel-flow drying method. In some embodiments, the inlet air temperature for spray drying is 200℃-300℃, further 200℃-220℃, 220℃-250℃, 250℃-280℃, or 250℃-300℃, specifically 200℃, 220℃, 250℃, 280℃, or 300℃; the outlet air temperature for spray drying is 100-200℃, further 100℃-110℃, 110℃-120℃, 120℃-150℃, or 150℃-200℃, specifically 100℃, 110℃, 120℃, 150℃, or 200℃.

[0047] Specifically, the mixed sol is atomized to form atomized droplets. These droplets descend in parallel with hot air, where almost all the water in the droplets evaporates instantly, forming a porous high-entropy metal salt composite precursor powder. The atomized sol, produced by spray drying, has a large specific surface area. The intense heat exchange between the atomized droplets and the hot air allows for rapid removal of water from the droplets, resulting in the desired porous high-entropy metal salt composite precursor powder. The high-entropy metal salt composite precursor powder obtained through spray drying atomization has advantages such as uniform particle size distribution, good flowability, good processability, and regular morphology.

[0048] Step S2 involves sintering the high-entropy metal salt composite precursor powder into a high-entropy bulk structure. This high-temperature solid-state reaction forms a stable, highly crystalline, high-entropy layered structure, ensuring the material's structural stability and uniformity. In step S2, the high-entropy metal salt composite precursor powder undergoes primary sintering. Specifically, the powder is placed inside a crucible and heated to 400℃-700℃ at a heating rate of 4-6℃ / min, then held at that temperature for 1-3 hours. In some embodiments of the present invention, the heating rate is 4-6°C / min, further 4-5°C / min, 5-5.5°C / min, or 5-6°C / min, specifically 4°C / min, 4.5°C / min, 5°C / min, 5.2°C / min, 5.4°C / min, or 6°C / min; heating to 400°C-700°C, further 400°C-600°C, 500°C-650°C, or 500°C-700°C, specifically 400°C, 420°C, 500°C, 510°C, 600°C, 640°C, or 700°C; holding at this temperature for 1-3 h, further 1-2 h, 1.5-2.5 h, or 2-3 h, specifically 1 h, 1.5 h, 2 h, or 3 h. Primary sintering can effectively remove organic matter and complexing agents from the surface of the high-entropy metal salt composite precursor.

[0049] In step S2 above, after the high-entropy metal salt composite precursor powder completes the primary sintering, it is further heated to 800-1000℃ at a heating rate of 2-4℃ / min and calcined for 11-13 h. The heating rate of 2-4℃ / min can specifically be 2℃ / min, 2.5℃ / min, 2.8℃ / min, 3℃ / min, 3.2℃ / min, 3.5℃ / min, 3.8℃ / min, or 4℃ / min. The temperature is then raised to 800℃-1000℃, specifically 800℃-1000℃, 900℃-980℃, or 850℃-1000℃, and further can be 800℃, 820℃, 900℃, 910℃, 950℃, 980℃, or 1000℃. The calcination time is 11-13 h, which can be further extended to 11-12 h, 11.5-12.5 h, 11.5-12 h, or 12-13 h. Oxygen needs to be added for calcination, with an oxygen flow rate of 80-150 ml / min. Specifically, the oxygen flow rate can be 80-100 ml / min, 90-150 ml / min, or 100-150 ml / min, which can be further extended to 80 ml / min, 82 ml / min, 90 ml / min, 100 ml / min, 120 ml / min, or 150 ml / min.

[0050] In step S3 above, the MAX phase material is a material with a hexagonal layered crystal three-dimensional structure, and the standard formula of the MAX phase material is M.n+1 AX n The definitions and value ranges of each element in the MAX phase are clearly defined, determining its crystal structure and properties. M represents a transition metal element, mainly from groups 3-6 (such as Ti, Sc, V, Nb, Ta, Cr, Mo, etc.), and is the core framework element of MAX phase materials, bonded to X through strong chemical bonds. A represents a main group element, mainly from group 13 (Al, Ga, ln) and group 14 (Si, Ge, sn), with Al being the most common (Ti3AlC2, Ti2AlC). X represents C (carbon) and / or N (nitrogen), which can be C or N alone, or form carbonitrides (such as Ti4AlN3). n represents an integer, taking values ​​of 1, 2, 3, 4 (up to 5 in rare cases), corresponding to different crystal structure types (e.g., type 211 when n=1; type 312 when n=2; type 413 when n=3). Currently discovered MAX phase materials are mainly n=1, 2, and 3.

[0051] MX and atom layers are alternately stacked and bonded by strong chemical bonds. The resulting MXene nanosheets, obtained by chemically etching away the atom layers in the MAX phase, exhibit tight adhesion between layers. Multiple atomic layers (typically >5 layers) are stacked together by weak van der Waals forces, forming multilayer MXene nanosheets. Physical exfoliation (e.g., intercalation, ultrasound) separates the multilayer MXene nanosheets, yielding few-layer or single-layer MXene nanosheets. The general chemical formula of these few-layer or single-layer MXene nanosheets is M. n+1 X n T x T x This refers to the functional groups that adhere to the MXene surface after etching. In this invention, after etching the MAX phase material, intercalation and ultrasonic exfoliation are performed to achieve efficient exfoliation of the MAX phase and stable dispersion of the MXene nanosheet material, which serves as the subsequent coating medium.

[0052] The MXene dispersion includes Ti3C2T x V2CT x V2NT x Mo2CT x Ti4N3T x Nb4C3T x One or more of them. Among them, Ti3C2T x For example, Ti3C2T xTi3C2 is the general chemical formula for two-dimensional (2D) nanomaterials composed of transition metal carbides, nitrides, or carbonitrides, and is the fixed stoichiometric structure of the MXene material matrix. Further, in some embodiments, the MXene dispersion may be further composed of Nb2CT. x Materials of the general formula also include novel materials such as transition metals like W, Mo, and Cr. In this invention, Ti3C2T is used as an example. x Let's take an example to illustrate.

[0053] In step S3, the MAX phase material is etched using an etching solution. The etching conditions are as follows: the MAX phase material is added to an etching solution with a concentration of 30%-40%, and stirred at 30℃-40℃ for 40-48 hours. The etching solution is hydrofluoric acid or an acid solution containing fluorine salts. The concentration of the etching solution is 30%-40%, and can further be 30%-35%, 35%-38%, 34%-38%, 35%-40%, etc., specifically 30%, 32%, 35%, 38%, or 40%. The stirring temperature is 30℃-40℃, and can further be 30℃-32℃, 32℃-35℃, 34℃-38℃, 35℃-40℃, etc., specifically 30℃, 32℃, 35℃, 38℃, or 40℃. The stirring time is 40-48 h, which can be further extended to 40-42 h, 40-44 h, 42-45 h, 45-48 h, etc. Specifically, it can be 40 h, 42 h, 44 h, 45 h or 48 h.

[0054] In step S3, the intercalation method involves adding an intercalating agent. This intercalating agent can embed itself between the layers of MXene. The embedding of the intercalating agent mechanically increases the interlayer spacing of MXene and weakens the van der Waals forces between the layers, making the layers easier to separate. The intercalating agent can be an organic molecule, such as tetramethylammonium hydroxide, tetrabutylammonium hydroxide, or n-butylamine; it can also be an inorganic salt solution, such as lithium chloride; or it can be metal ions such as sodium, potassium, calcium, magnesium, aluminum, or zinc. In this invention, tetrabutylammonium hydroxide is used as an example.

[0055] In step S3, the ultrasonic ablation process is performed at a power of 300-400W for 2-3 hours. The power is 300-400W, but in some embodiments of the invention, it can be further 300-350W, 320-350W, 340-380W, 350-400W, etc., specifically 300W, 320W, 340W, 350W, 380W, or 400W. The ultrasonic ablation time is 2-3 hours, but in some embodiments of the invention, it can be further 2-2.5 hours, 2.2-2.4 hours, 2.5-2.8 hours, 2.5-3 hours, etc., specifically 2 hours, 2.2 hours, 2.4 hours, 2.5 hours, 2.8 hours, or 3 hours.

[0056] Step S4 further includes: The high-entropy material with a layered structure is mixed with the MXene dispersion at a first mass ratio, followed by centrifugation and vacuum drying to form a chemically bonded MXene coating layer, thus obtaining a primary MXene-coated high-entropy material; and The MXene primary coated high-entropy material is mixed with the MXene dispersion at a second mass ratio, ultrasonicated at room temperature, and then freeze-dried to complete the physical adsorption to form the MXene gradient coating layer, thus obtaining the MXene coated high-entropy bulk material.

[0057] In step S4, an MXene gradient coating layer is constructed sequentially through chemical bonding and physical adsorption, which effectively improves the electronic conductivity and interface stability of the prepared MXene-coated high-entropy bulk material.

[0058] Further, in the specific steps of step S4 above, the high-entropy material with a layered structure is mixed with the MXene dispersion at a first mass ratio under stirring at 50℃-60℃ for 5-6 h; then centrifuged at 5000-6000 rpm for 5-6 min to separate the primary MXene-coated high-entropy material from the MXene dispersion, and vacuum dried at 80℃-90℃ for 10-12 h to obtain a stable chemically bonded MXene coating. The primary MXene-coated high-entropy material is then added back into the MXene dispersion and mixed at a second mass ratio, and ultrasonically treated at room temperature for 30-40 min to allow the MXene material to be physically adsorbed onto the surface of the primary MXene-coated high-entropy material through van der Waals forces and hydrogen bonds; finally, a complete MXene gradient coating layer is formed by freeze-drying at -50℃ to -60℃ for 20-24 h.

[0059] Wherein, the first mass ratio is 1:(18-22), and in some embodiments of the present invention, it may further be 1:(18-19), 1:(19-20), 1:(18-20), 1:(20-22), etc., specifically 1:18, 1:19, 1:20, 1:21 or 1:22. The second mass is 1:(0.1-0.3), and in some embodiments of the present invention, it may further be 1:(0.1-0.2), 1:(0.15-0.25), 1:(0.2-0.3), etc., specifically 1:0.1, 1:0.15, 1:0.2 or 1:0.3.

[0060] In step S4, the mixing conditions are stirring at 50℃-60℃ for 5-6 hours. In some embodiments of the present invention, the stirring temperature is 50℃-60℃, and can further be 50℃-55℃, 52℃-54℃, 54℃-58℃, 55℃-60℃, etc., specifically 50℃, 52℃, 55℃, 58℃, or 60℃. The stirring time is 5-6 hours, and can further be 5-5.2 hours, 5.2-5.5 hours, 5.5-5.8 hours, or 5.5-6 hours, specifically 5 hours, 5.2 hours, 5.4 hours, 5.5 hours, 5.8 hours, or 6 hours.

[0061] In step S4, the centrifugation conditions are centrifugation at 5000-6000 rpm for 5-6 minutes. In some embodiments of the present invention, the centrifugation speed is 5000-6000 rpm, and can further be 5000-5200 rpm, 5200-5500 rpm, 5400-5800 rpm, 5500-6000 rpm, etc., specifically 5000 rpm, 5200 rpm, 5400 rpm, 5500 rpm, 5800 rpm, or 6000 rpm. The centrifugation time is 5-6 minutes, and can further be 5-5.2 minutes, 5.2-5.5 minutes, 5.5-6 minutes, etc., specifically 5 minutes, 5.2 minutes, 5.5 minutes, or 6 minutes.

[0062] In step S4, the vacuum drying temperature is 80℃-90℃. In some embodiments of the present invention, it can be further 80℃-82℃, 82℃-85℃, 85℃-88℃, 85℃-90℃, etc., specifically 80℃, 82℃, 85℃, 88℃, or 90℃. The vacuum drying time is 10-12 h, further 10-10.5 h, 10.2-10.5 h, 10.5-11 h, 11-12 h, etc., specifically 10 h, 10.2 h, 10.5 h, 11 h, 11.5 h, or 12 h.

[0063] In step S4, the freeze-drying temperature is -50℃ to -60℃. In some embodiments of the present invention, it may further be -50℃ to -55℃, -52℃ to -55℃, -54℃ to -58℃, -55℃ to -60℃, etc., specifically -50℃, -52℃, -55℃, or -60℃. The freeze-drying time is 20-24 h, further including 20-21 h, 20-22 h, 20-23 h, 23-24 h, etc. Specifically, it may be 20 h, 21 h, 22 h, 23 h, or 24 h.

[0064] Step S5 primarily involves high-temperature annealing to eliminate surface defects in MXene, thereby improving the conductivity of the coating layer and the stability of the interfacial bonding. In step S5, the first temperature is 300℃-500℃. In some embodiments of the present invention, it can be further set to 300℃-350℃, 340℃-380℃, 420℃-480℃, 450℃-500℃, etc., specifically 300℃, 340℃, 350℃, 400℃, 450℃, or 500℃. The second temperature is 600℃-700℃. In some embodiments of the present invention, it can be further set to 600℃-620℃, 600℃-650℃, 620℃-650℃, 650℃-700℃, etc., specifically 600℃, 620℃, 640℃, 650℃, or 700℃.

[0065] In step S5, the preset time is 2-3 hours. In some embodiments of the present invention, it can be further 2-2.2 hours, 2.2-2.5 hours, 2.4-2.8 hours, 2.5-3 hours, etc., specifically 2 hours, 2.2 hours, 2.4 hours, 2.5 hours, or 3 hours. The reduction treatment time is 1-2 hours. In some embodiments of the present invention, it can be further 1-1.2 hours, 1.2-1.6 hours, 1.5-2 hours, etc., specifically 1 hour, 1.2 hours, 1.5 hours, 1.6 hours, or 2 hours. In step S5, the protective atmosphere can be high-purity argon, and the reducing atmosphere can be a hydrogen / argon (5% H2) mixed gas atmosphere.

[0066] In order to better illustrate the MXene-coated high-entropy composite cathode material, its preparation method, and the effects on lithium batteries claimed in this invention, the following experimental examples and comparative examples are used for comparison and explanation.

[0067] Experimental Example 1 Step 1: Preparation of high-entropy metal salt composite precursor powder Weigh out the lithium-rich manganese-based precursor and various high-entropy doped metal salts (Ni(NO3)2, Cr(NO3)3, Mg(NO3)2, Fe(NO3)3, Al(NO3)3) according to the design ratio, and mix them in deionized water at a molar ratio of 1:1 to ensure the initial uniform distribution of metal elements in the solution. Citric acid was added to the mixed solution as a complexing agent, and the molar ratio of citric acid to metal ions was controlled at 1.5:1. The mixture was continuously magnetically stirred at 60°C for 4 hours to form a stable, transparent, homogeneous metal complex sol. The obtained sol was processed by a spray dryer (inlet air temperature 200℃, outlet air temperature 100℃) to obtain a high-entropy metal salt composite precursor powder with good flowability, which was then set aside.

[0068] Step 2: High-temperature solid-state reaction The precursor powder obtained in step 1 was evenly spread in an alumina crucible, placed in a muffle furnace, and heated to 500°C at a heating rate of 5°C / min in air atmosphere, and held for 2 h to fully remove organic residues and complexing agents. Continue to raise the temperature to 900℃ at 3℃ / min, and calcine for 12 h under continuous oxygen supply (100 mL / min) to allow the metal elements to fully react and form a high-entropy lithium-rich manganese base layer structure. The calcined product was naturally cooled to room temperature and then pulverized by planetary ball milling (300 rpm, 6 h) to obtain the target high-entropy lithium-rich manganese-based material.

[0069] Step 3: Preparation of MXene dispersion Ti3AlC2MAX phase powder was added to a 40% hydrofluoric acid solution (solid-liquid ratio 1:20) and magnetically stirred in a polytetrafluoroethylene container at 35°C for 48 h to remove the Al layer and release the Ti3C2 layered structure. The product was washed by centrifugation with deionized water (3500 rpm, 5 min) multiple times until the pH of the supernatant was >6; tetrabutylammonium hydroxide (TBAOH) was added for intercalation treatment, and after standing for 12 h, ultrasonic exfoliation was performed for 2 h (power 300W, intermittent mode) to form a single-layer / few-layer Ti3C2 nanosheet dispersion. The stripped solution was vacuum filtered to collect the MXene dispersion for later use, with the concentration controlled below 2 mg / mL to maintain good stability.

[0070] Step 4: Construction of the gradient overlay layer Inner layer chemical bonding construction: The high-entropy material obtained in step 2 was added to Ti3C2 dispersion at a mass ratio of 1:20 and magnetically stirred at 60℃ for 6 h; then centrifuged (5000 rpm, 5 min) to separate and vacuum dried at 80℃ for 12 h to obtain a stable chemically bonded MXene coating. External physical adsorption enhancement: The dried product was added back into the Ti3C2 dispersion and mixed at a mass ratio of 1:0.1. The mixture was then ultrasonically treated at room temperature for 30 minutes to allow the multilayer MXene to be physically adsorbed onto the material surface through van der Waals forces and hydrogen bonds. Finally, a complete gradient MXene coating layer was formed by freeze drying (-50℃, 24 h).

[0071] Step 5: High-temperature annealing optimization The coated composite material was placed in a quartz tube furnace and a protective atmosphere of high-purity argon gas (200 mL / min) was introduced. The temperature was increased to 400℃ at 2℃ / min and held for 2 hours to remove surface adsorbed water and structural defects. Continue heating to 600℃, switch to a hydrogen / argon (5% H2) mixed gas atmosphere, and hold for 1 hour to further reduce the oxygen-containing functional groups on the MXene surface and enhance its electronic conductivity and interfacial bonding strength. After natural cooling to room temperature, a gradient-coated high-entropy lithium-rich manganese-based composite cathode material with stable structure and excellent conductivity was finally obtained.

[0072] Please see Figure 5 The figure shows the XRD pattern (X-ray diffraction) of the MXene-coated high-entropy composite cathode material obtained in Experimental Example 1 provided by the present invention. The figure shows a typical layered structure, and the peak broadening indicates multi-element solid solution. The corresponding MXene interlayer spacing is significantly increased, confirming the successful MXene gradient coating.

[0073] Experiment Example 2 In Experiment Example 1, the high-entropy doped metal salts in step 1 were changed to Co(NO3)2, Fe(NO3)3, Mg(NO3)2, Ni(NO3)2, and Cr(NO3)3, while the other experimental conditions and steps were completely consistent with those in Experiment Example 1.

[0074] Experimental Example 3 In Experiment Example 1, the high-entropy doped metal salts in step 1 were changed to Co(NO3)2, Fe(NO3)3, Cu(NO3)2, Ni(NO3)2, and Cr(NO3)3, while the other experimental conditions and steps were completely consistent with those in Experiment Example 1.

[0075] Experiment Example 4 In Experiment Example 1, the MAX phase material in step 3 was changed to Ti4GaC3, while the other experimental conditions and steps were completely consistent with those in Experiment Example 1.

[0076] Experimental Example 5 In Experiment Example 1, the MAX phase material in step 3 was changed to V2GaC, while the other experimental conditions and steps were completely consistent with those in Experiment Example 1.

[0077] Comparative Example 1 No MXene gradient coating layer is formed, i.e. steps 3 to 5 are omitted. Other experimental conditions and steps are completely consistent with those in Experiment 1.

[0078] Comparative Example 2 Without forming a high-entropy layered structure material, i.e. without going through steps 1 and 2, the other experimental conditions and steps are completely consistent with those in Experimental Example 1. An MXene gradient coating layer is directly constructed on the surface of a lithium-rich manganese-based precursor using an MXene dispersion.

[0079] The MXene-coated high-entropy composite cathode materials obtained in Experiments 1-5 and the cathode materials obtained in Comparative Examples 1 and 2 were assembled into coin half-cells, and their capacity retention after 600 cycles was measured to compare their superior performance. Table 1 shows the test results of the capacity retention of the above experimental examples and comparative examples.

[0080] Determination of capacity retention: The MXene-coated high-entropy composite cathode materials obtained in Experiments 1-5 and the cathode materials obtained in Comparative Examples 1 and 2 were assembled into coin cell half-cells. The cells were charged at a constant current of 1C to the cutoff voltage, and then discharged at a constant current of 1C to the cutoff voltage, undergoing 600 charge-discharge cycles. Capacity retention rate = (Specific capacity at discharge cycle 600 / Specific capacity at discharge cycle 1) × 100%.

[0081] Table 1. Performance data of experimental examples and comparative examples.

[0082] The MXene-coated high-entropy composite cathode materials in Examples 1-5 were prepared using the complete process flow of the MXene-coated high-entropy composite cathode material preparation method provided by this invention. The half-cells assembled using the MXene-coated high-entropy composite cathode materials in Examples 1-5 all exhibited a capacity retention rate of over 90% after 600 cycles, which is significantly higher than that of Comparative Example 1 (78.19%) without MXene coating and Comparative Example 2 (78.81%) without high-entropy drive. This indicates that the MXene-coated high-entropy composite cathode materials prepared using the MXene-coated high-entropy composite cathode material preparation method provided by this invention have better cycle performance.

[0083] The foregoing has provided a detailed description of an MXene-coated high-entropy composite cathode material, its preparation method, and a lithium battery disclosed in the embodiments of the present invention. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention. Any modifications, equivalent substitutions, and improvements made within the principles of the present invention should be included within the protection scope of the present invention.

Claims

1. An MXene-coated high-entropy composite cathode material, characterized in that, It comprises a high-entropy layered structure material and an MXene gradient coating layer, wherein the MXene gradient coating layer is sequentially coated on the high-entropy layered structure material through chemical bonding and physical adsorption; wherein the high-entropy layered structure material comprises a lithium-rich manganese-based precursor and a high-entropy doped metal salt, wherein the metal in the high-entropy doped metal salt includes at least five of the following: Cu, Fe, Mo, Ag, Au, Al, Mg, Nb, Hf, Ta, Cr, and Ge, and the high-entropy layered structure material is formed by sintering porous high-entropy metal salt composite precursor powder; the material of the MXene gradient coating layer includes Ti3C2T. x V2CT x V2NT x Mo2CT x Ti4N3T x Nb4C3T x One or more combinations thereof; The MXene gradient coating layer is sequentially coated onto the high-entropy layered structure material through chemical bonding and physical adsorption. Specifically, the high-entropy material with a layered structure is mixed with an MXene dispersion at a first mass ratio of 1:(18-22) at 50℃-60℃ for 5-6 h, followed by centrifugation and vacuum drying to form a chemically bonded MXene coating layer, thus obtaining a primary MXene-coated high-entropy material. The primary MXene-coated high-entropy material is then mixed with the MXene dispersion at a second mass ratio of 1:(0.1-0.3), ultrasonically treated at room temperature, and then freeze-dried to complete physical adsorption, thus forming the MXene gradient coating layer and obtaining the MXene-coated high-entropy bulk material.

2. The MXene-coated high-entropy composite cathode material as described in claim 1, characterized in that, The thickness of the MXene gradient coating layer is 2-20 nm.

3. A method for preparing an MXene-coated high-entropy composite cathode material, characterized in that, Specifically, the following steps are included: A lithium-rich manganese-based precursor was mixed with a high-entropy doped metal salt, a complexing agent was added and stirred to form a sol, and then spray-dried to obtain a porous high-entropy metal salt composite precursor powder. The porous high-entropy metal salt composite precursor powder is subjected to primary sintering, followed by secondary sintering, cooling, and ball milling to obtain a high-entropy layered structure material. MAX phase material and etching solution are provided. The MAX phase material is etched with the etching solution and then intercalated and ultrasonically exfoliated to obtain an MXene dispersion containing monolayer or few-layer MXene nanosheet material. The high-entropy material with a layered structure is mixed with the MXene dispersion at a first mass ratio of 1:(18-22) at 50℃-60℃ for 5-6 h, then centrifuged and vacuum dried to form a chemically bonded MXene coating layer to obtain the MXene primary coated high-entropy material; the MXene primary coated high-entropy material is mixed with the MXene dispersion at a second mass ratio of 1:(0.1-0.3), ultrasonically treated at room temperature, and then freeze-dried to complete the physical adsorption to form the MXene gradient coating layer to obtain the MXene coated high-entropy bulk material; as well as After heating the MXene-coated high-entropy bulk material to a first temperature under a protective atmosphere and maintaining it for a preset time, it was then heated to a second temperature under a reducing atmosphere for reduction treatment and cooled to room temperature to obtain the MXene-coated high-entropy composite cathode material. The MXene-coated high-entropy composite cathode material as described in claim 1 was prepared.

4. The method for preparing an MXene-coated high-entropy composite cathode material according to claim 3, characterized in that, In the step of mixing a lithium-rich manganese-based precursor with a high-entropy doped metal salt, adding a complexing agent and stirring to form a sol, and then spray drying to obtain a high-entropy metal salt composite precursor powder: The molar ratio of the lithium-rich manganese-based precursor to the high-entropy doped metal salt is 1:(0.8-1.2), the molar ratio of the complexing agent to the metal in the high-entropy doped metal salt is (1.4-1.6):1; and / or, the inlet air temperature of the spray drying process is 200℃-300℃, and the outlet air temperature is 100℃-200℃.

5. The method for preparing an MXene-coated high-entropy composite cathode material according to claim 3, characterized in that, In the process of primary sintering of high-entropy metal salt composite precursor powder followed by secondary sintering: The primary sintering conditions are as follows: heating to 400℃-700℃ at a heating rate of 4-6℃ / min, and holding at that temperature for 1-3 hours. The secondary sintering conditions are as follows: under oxygen-bearing conditions, the temperature is increased to 800℃-1000℃ at a heating rate of 2-4℃ / min, and calcined for 11-13 h.

6. The method for preparing an MXene-coated high-entropy composite cathode material according to claim 3, characterized in that, In the steps of providing MAX phase material and etching solution, etching the MAX phase material with the etching solution, and obtaining an MXene dispersion containing monolayer or few-layer MXene nanosheets through intercalation and ultrasonic exfoliation, the etching conditions are as follows: adding the MAX phase material to an etching solution with a concentration of 30%-40% and stirring at 30℃-40℃ for 40-48 h; the etching solution is hydrofluoric acid or an acid solution containing fluorine salts; and / or... The ultrasonic ablation process is performed at a power of 300-400W for 2-3 hours.

7. The method for preparing an MXene-coated high-entropy composite cathode material according to claim 3, characterized in that, In the step of heating the MXene-coated high-entropy bulk material to a first temperature under a protective atmosphere and holding it for a preset time, then heating it to a second temperature under a reducing atmosphere for reduction treatment, and finally cooling it to room temperature to obtain the MXene-coated high-entropy composite cathode material: The first temperature is 300-500℃, the second temperature is 600-700℃; and / or, the preset time is 2-3 hours, and the reduction treatment time is 1-2 hours.

8. The method for preparing an MXene-coated high-entropy composite cathode material according to claim 3, characterized in that, The centrifugation conditions are 5000-6000 rpm for 5-6 min, the vacuum drying conditions are 80℃-90℃ for 10-12 h, and the freeze-drying conditions are -50℃ to -60℃ for 20-24 h.

9. A lithium battery, the lithium battery comprising the MXene-coated high-entropy composite cathode material as described in any one of claims 1 and 2, or the MXene-coated high-entropy composite cathode material prepared by the preparation method of the MXene-coated high-entropy composite cathode material as described in any one of claims 3-8.

Citation Information

Patent Citations

  • Lithium-rich manganese-based composite positive electrode material optimized by adopting Mxene and preparation method of lithium-rich manganese-based composite positive electrode material

    CN114944481A

  • High-entropy cobalt-free lithium-rich manganese-based positive electrode material as well as preparation method and application thereof

    CN120483279A